Formulation of Composite Flour with Antioxidant from Goroho Plantain Flour (Musa Acuminafe, sp) and Yellow Pumpkin Flour (Cucurbita moschata) and Its Application on Biscuit Making - Imanuel Medy Pasanda; Edi Suryanto; Gregoria Djarkasi (Indonesian Food and Nutrition Progress, 2019)
Locally grown crops with phytochemical antioxidant content i.e. goroho plantain and yellow pumpkin were used to develop composite flour. Mixture experiment with simplex lattice design was used for formulation to study the effect of blending goroho plantain flour (GF) with yellow pumpkin flour (PF) on phytochemical content and antioxidant capacity of developed composite flours. Responses measured including phytochemical content (total phenolic and carotenoid), antioxidant capacity (DPPH assay, FRAP assay, phosphomolybdenum assay, and reducing power assay), colour values of flours, proximate components, and sensory quality of biscuits made from composite flours. The results showed that increase in proportion of PF improved the phytochemical content, antioxidant capacity, and proximate components with the exception of carbohydrates. However, substitution of GF with PF reduced sensory ratings for all the sensory attributes of biscuits developed from composite flours. Among biscuits made from composite flours, sensory ratings for aroma, colour, texture, and taste were not statistically different (p>0.05). PF can be used as fortification material to improve the phytochemical antioxidant content in composite flours prepared from GF and PF, or flours from other locally grown plants.